Determination of the band gap energy for ternary material Sn-In-Zn-O thin films by electron spectroscopy and ultra-visible spectrometer - Yus Rama Denny (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2015)
The SnInZnO thin film was prepared at room temperature by RF magnetron sputtering. The band gap of this film was investigated by REELS and UV-Spectrometer analysis. By using REELS with low energy (500 eV) and high energy (1500 eV) electron beams, the surface band gap as well as and the bulk energy band gap were measured. The result shows that the band gaps are affected by the primary electron energies. The transmittance value of 80% in the visible light region has been achieved. The optical band gap was calculated by using Tauc’s relation from UV-Spectrometer analysis and compared to that of the band gap obtained by the REELS spectra.